Ice-inhabiting species of Bdelloidea Rotifera reveal a pre-Quaternary ancestry in the Arctic cryosphere - Shain, Daniel H.; Rogozhina, Irina; Fontaneto, Diego; Nesje, Atle; Saglam, Naim; Bartlett, Jesamine; Rosvold, Jorgen (Royal Soc, 2024)
Historical climate data indicate that the Earth has passed through multiple geological periods with much warmer-than-present climates, including epochs of the Miocene (23-5.3 mya BP) with temperatures 3-4 degrees C above present, and more recent interglacial stages of the Quaternary, for example, Marine Isotope Stage 11c (approx. 425-395 ka BP) and Middle Holocene thermal maximum (7.5-4.2 ka BP), during which continental glaciers may have melted entirely. Such warm periods would have severe consequences for ice-obligate fauna in terms of their distribution, biodiversity and population structure. To determine the impacts of these climatic events in the Nordic cryosphere, we surveyed ice habitats throughout mainland Norway and Svalbard ranging from maritime glaciers to continental ice patches (i.e. non-flowing, inland ice subjected to deep freezing overwinter), finding particularly widespread populations of ice-inhabiting bdelloid rotifers. Combined mitochondrial and nuclear DNA sequencing identified approx. 16 undescribed, species-level rotifer lineages that revealed an ancestry predating the Quaternary (> 2.58 mya). These rotifers also displayed robust freeze/thaw tolerance in laboratory experiments. Collectively, these data suggest that extensive ice refugia, comparable with stable ice patches across the contemporary Norwegian landscape, persisted in the cryosphere over geological time, and may have facilitated the long-term survival of ice-obligate Metazoa before and throughout the Quaternary.
Keywords: ice; evolution; microinvertebrate; rotifer; climate change; Norway